Association of familial Mediterranean fever and epicardial adipose tissue: A systematic review and meta‐analysis. Issue 4 (13th June 2022) - Motawea, Karam R.; Kandil, Omneya A.; Varney, Joseph; Aboelenein, Merna; Ibrahim, Nancy; Shaheen, Ahmed; Khairy, Lina T.; Bakkour, Agyad; Muwaili, Ali H. H.; Muwaili, Dhuha H. H.; Abdelmajid, Fatima A. A.; Ahmad, Eman M. S.; et al.
Abstract: Background and Aim: Some studies reported a positive link between familial Mediterranean fever (FMF) and epicardial adipose tissue. Our meta‐analysis aimed to evaluate whether there is a significant association between FMF and increased epicardial adipose tissue thickness. Methods: We searched the following databases: PUBMED, WOS, OVID, SCOPUS, and EMBASE. Inclusion criteria were any original articles that reported epicardial adipose tissue in FMF patients with no age restriction, excluding reviews, case reports, editorials, animal studies, and non‐English studies. Thirty eligible studies were screened full text but only five studies were suitable. We used RevMan software (5.4) for the meta‐analysis. Results: The total number of patients included in the meta‐analysis in the FMF patients group is 256 (mean age = 24.3), and the total number in the control group is 188 (mean age = 24.98). The pooled analysis between FMF patients and controls was [mean difference = 0.82 (95% CI = 0.25–1.39), p ‐value = 0.005]. We observed heterogeneity that was not solved by random effects ( p  > 0.00001). We performed leave one out test by removing the Kozan et al. study, and the heterogeneity was solved ( p  = 0.07), and the results were (MD = 0.98, 95% CI = 0.52–1.43, p ‐value < 0.0001). Conclusion: FMF patients are at increased risk of developing epicardial adipose tissue compared to controls. More multicenter studies with higher sample sizes are needed to support our results.